STRATEGIC PLANNING OF INFORMATION AND TECHNOLOGY SYSTEMS OF INDONESIAN NAVAL ACADEMY - Isnadi Isnadi; Suparno Suparno; I Nengah Putra; Benny Sukandari (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
Information technology (IT) has an important role in carrying out the functions of universities, so that it can be trusted to increase the efficiency and effectiveness of the academic process lead to the academic services being more maximal as well as supporting the university's business process innovation to develop. The Naval Academy (AAL) is one of the educational institutions found in the Indonesian Navy and has the task of producing professional Navy officers, possessing current technological mastery capabilities and towards World Class Navy. By referring to the desired results above, AAL uses information technology in conducting teaching and learning activities. The Information System available at the Naval Academy (AAL) is currently not optimal, therefore the authors conducted an analysis to plan the strategic development of information systems and information technology at the Naval Academy (AAL). This research was made using the Ward and Peppard method. The step of this research started with internal analysis, external analysis using PEST analysis, internal IS/IT analysis and external SI/IT analysis to map the information system position at the Naval Academy (AAL) with SWOT analysis. The results were the achievement of the IS/IT formulation strategy and management of IS/IT in the future